2014
DOI: 10.1051/e3sconf/20140301002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Significant Causes to School Building Defects

Abstract: Abstract. This paper focuses on the contribution factors of building defects in Malaysian school buildings. There are several building defects commonly found in Malaysia school buildings. In fact, building defects are becoming ordinary phenomena in the construction industry which results in negative impacts on schools, in the means of building performance, health and safety aspects and overall environment conditions as well as teaching and learning processes. Thus, a study is planned to identify the common bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…2 illustrate the result of frequency and percentages (%) for the satisfaction level of school building performance obtained in various spaces, including the classroom, office, laboratory, library, canteen, and others. Students and teachers have used the spaces in the school buildings to a large extent; as a result, defects are usually attributed to aging factors, user behaviours, and adverse weather conditions (Talib et al 2014: Mydin et al, 2014) that affected the level of satisfaction. Therefore, based on the statistical differences between users' satisfaction levels, the toilet recorded the highest percentage of dissatisfaction at 58.33%.…”
Section: The Level Of Satisfaction On School Building Performancementioning
confidence: 99%
See 1 more Smart Citation
“…2 illustrate the result of frequency and percentages (%) for the satisfaction level of school building performance obtained in various spaces, including the classroom, office, laboratory, library, canteen, and others. Students and teachers have used the spaces in the school buildings to a large extent; as a result, defects are usually attributed to aging factors, user behaviours, and adverse weather conditions (Talib et al 2014: Mydin et al, 2014) that affected the level of satisfaction. Therefore, based on the statistical differences between users' satisfaction levels, the toilet recorded the highest percentage of dissatisfaction at 58.33%.…”
Section: The Level Of Satisfaction On School Building Performancementioning
confidence: 99%
“…The second most important factor is the scheduled maintenance approach, with a mean value of 3.72. Strategic maintenance is needed for school buildings to ensure its functional regularity instead of corrective or emergency maintenance work (Mydin et al 2014) Ample literature has shown that building has an impact on user experience; therefore, physical aspects are relevant to improving the overall performance of school buildings. The following are the essential physical requirements that are significantly applicable to the Post Occupancy Evaluation (POE) of the school building.…”
Section: The Factors Of Post Occupancy Evaluation (Poe) Implementatio...mentioning
confidence: 99%
“…The second most important factor is the scheduled maintenance approach, with a mean value of 3.72. Strategic maintenance is needed for school buildings to ensure its functional regularity instead of corrective or emergency maintenance work (Mydin et al 2014). The lowest mean value was recorded by accessibility (0.86) followed by sufficient facilities (1.31) are not highly significant factors since the Department of Public Works (PWD) defines most corrective requirements, and also because of fewer deficiencies highlighted by the surveyed-respondents (Anselm et al,2018).…”
Section: The Factors Of Post Occupancy Evaluation (Poe) Implementatio...mentioning
confidence: 99%
“…Thus, due to the high cost of maintenance, some school buildings limit their building usage to ensure safety and health among students and teachers. The poor condition of school buildings had a direct impact on the student’s satisfaction and comfort levels during the learning activities (Mydin et al , 2014). In other countries, such as The Netherlands, the finance structure for school buildings has been divided into two budgets, initial costs of new buildings and maintenance or repair because of many school buildings either primary or secondary are already old, poorly maintained and have a poor indoor environment quality (Jong and Arkesteijn, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%